Recycling of post-consumption food waste through pyrolysis: Feedstock characteristics, products analysis, reactor performance, and assessment of worldwide implementation potentials. (15th November 2022) - Makkawi, Yassir; Hassan Pour, Fatemeh; Elsayed, Yehya; Khan, Muhammad; Moussa, Omar; Masek, Ondrej; Badrelzaman, Mohamed; El Tahir, Wasil
Graphical abstract: Highlights: Pyrolysis of post-consumption food waste has been conducted in an auger reactor. Pyrolysis yield was 37.2% bio-oil, 27.6% char, 21.0% gas, and 14.2% aqueous phase. Bio-oil has low water content, is nearly alkaline, and has HHV = 28.2 MJ kg −1 . Bio-oil consisted of fatty acids commonly found in dairy, meat, and vegetable oils. Food wase pyrolysis is predicted to contribute 30% to the world's renewables by 2026. Abstract: Food waste produced in households, public restaurants, and hospitality sectors is causing serious concerns due to its negative environmental impact and the associated cost of disposal in landfills. This paper presents a comprehensive experimental assessment of post-consumption food waste characteristics, its conversion to added-value products through pyrolysis, and its potentials for worldwide large-scale processing. Analysis of the food waste samples revealed highly desirable features (e.g., volatile = 75.2%, lipid = 15.4%, and HHV = 20.1 MJ kg −1 ). The overall pyrolysis yield was 37.2% bio-oil, 14.2% aqueous phase, 27.6% biochar, and 21.0% non-condensable gas. The bio-oil showed attractive fuel characteristics (HHV = 28.2 MJ kg −1, water content = 4.6%, and pH = 6), however, the viscosity was high (136 cSt). The most abundant compounds in the bio-oil were major fatty acids commonly found in dairy fats, meat, and hydrogenated vegetable oils. The biochar has an improved characteristic (HHV = 26.3 MJ kg −1 and O/C = 0.065), which makes it potentially useful for energy applications as well as for long-term carbon sequestration if used in soil amendment. The non-condensable gas has an energy content of 15.8 MJ kg −1, nearly 30% that of natural gas. In assessing the worldwide potential implementation of food waste pyrolysis, the calculations indicate that Eastern and Southern Asia, followed by sub-Saharan Africa, respectively, are of the highest potential for large-scale processing. The estimated world's energy output is 1376.2 GW and this is predicted to contribute to around 30% to the world's demand of renewable energies by 2026, if this feedstock is fully utilized. Most importantly, the outcome of this study is highly encouraging for the development of bioenergy technology in regions where conventional biomass resources are limited, such as arid and semi-arid regions.